2023
DOI: 10.1007/s00705-023-05751-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-epidemiological survey of feline parvovirus circulating in three Egyptian provinces from 2020 to 2021

Abstract: Feline parvovirus infection, caused by feline parvovirus and canine parvovirus 2, is a highly contagious, life-threatening disease affecting cats. The available epidemiological data on parvovirus infection in cats in Egypt is limited. Therefore, the aim of the current study was to provide data concerning the epidemiological profile of cats infected with parvovirus, including the prevalence of parvovirus infection in cats in three Egyptian provinces (Sohag, Assiut, and Cairo) and the associated risk factors. Us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Reviewing the previous studies, there are molecular characterization studies of CPV341 2 in Egypt. A lower prevalence of parvovirus (43% using PCR) (35% using IC test) was detected in an Egyptian study included three provinces (Cairo, Sohag and Assiut) (Abdel-Baky et al, 2023). Others (Zaher et al, 2020) also reported a lower prevalence of CPV-2 (40%) by rapid Ag Test Kit.…”
Section: Discussionmentioning
confidence: 92%
“…Reviewing the previous studies, there are molecular characterization studies of CPV341 2 in Egypt. A lower prevalence of parvovirus (43% using PCR) (35% using IC test) was detected in an Egyptian study included three provinces (Cairo, Sohag and Assiut) (Abdel-Baky et al, 2023). Others (Zaher et al, 2020) also reported a lower prevalence of CPV-2 (40%) by rapid Ag Test Kit.…”
Section: Discussionmentioning
confidence: 92%
“…Rectal swabs or fecal samples from the Central and Eastern China (2018–2022) showed 35.82% (48/134) positivity rate for FPV (77.08%, 37/48) or canine parvovirus type-2 (CPV-2) (22.92%, 11/48) [ 23 ]. Egyptian cats (2020–2021) showed 35% (35/100) positivity rate for FPV and 43% (43/100) positivity rate for CPV-2 [ 24 ]. Fecal samples of 1620 diarrheal cats from Korea (2016–2019) showed 29.37% (819/1620) and 7.49% (209/1620) positivity rates for FCoV and FPV, respectively [ 25 ].…”
Section: Discussionmentioning
confidence: 99%